Preliminary Study of Immobilized of Cellulase in Silica from the Rice Husk Ash to Hydrolysis Sugarcane Bagasse. Issue 1 (May 2019) - Utomo, Yudhi; Yuniawati, Nurakhma; Wonorahardo, Surjani; Sumari,; Santoso, Aman; Kartika Kusumaningrum, Irma; Susanti, Evi
Abstract: Cellulase in the production of bioethanol from sugarcane bagasse is used to hydrolyze cellulose into reducing sugars. Cellulase needs to be mobilized in a matrix to improve its efficiency because it can be used repeatedly. The purpose of this study was to conduct a preliminary study of potential cellulase immobilized on silica to hydrolyze sugarcane bagasse including the effect of contact time (15, 45, 60, and 75 minutes) and agitation speeds (50, 100, 150, and 200 rpm) on % immobilization and immobilized cellulase activity against sugarcane bagasse, and also decreased activity of immobilized cellulase after repeated use. Contact time and agitation speeds do not affect % immobilization. The optimum contact time and agitation speeds of immobilized cellulase formation based on its activity were at 15 minutes and 100 rpm. Immobilized cellulase activity in cycles II and III decreased to 75.2% and 58.8% compared to the first cycle. Therefore, immobilized cellulase in silica is good enough to hydrolyze sugarcane bagasse and has the potential to be applied as continue system in the production of bioethanol from sugarcane bagasse.